The Impact of PAD and TKDD on Regional Expenditure in South Sumatra - Roni Juliansyah; Sugiharto Sugiharto; Riza Syahputera; Yancik Syafitri; Nurhudawi (Jurnal Ilmiah Ekonomi Global Masa Kini, 2026)
This study aims to analyze the effect of Local Own-Source Revenue (PAD) and Transfers to Regions and Village Funds (TKDD) on local government expenditures in regencies and cities in South Sumatra Province for the 2020–2024 period. The study employs a quantitative approach using secondary data obtained from the Budget Implementation Reports of the Directorate General of Fiscal Balance of the Ministry of Finance of the Republic of Indonesia. The research sample is determined through purposive sampling, resulting in 17 regencies/cities, including Palembang City, Prabumulih City, Lahat Regency, Banyuasin Regency, and Musi Banyuasin Regency, with a total of 85 observations analyzed by multiple linear regression. The results indicate that PAD and TKDD simultaneously have a positive and significant effect on local government spending, explaining 43.1% of the model's variance. Partially, PAD has a positive and significant effect, but TKDD exerts a far more dominant influence, confirming the flypaper effect due to high local fiscal dependence on central government transfers. The practical implications highlight the critical need for local governments to optimize PAD independently through intensification, extensification, and digitalization of local tax systems. Furthermore, local governments must enhance management efficiency by prioritizing budget allocation toward productive expenditures that support public services. For the central government, these findings imply the necessity of periodic evaluations of transfer fund formulas to ensure better targeting, promote local fiscal autonomy, and minimize the risk of spending inefficiencies at the regional level.  Keywords: Local Own-Source Revenue (PAD), Transfers to Regions and Village Funds (TKDD), Local Government Expenditures, Fiscal Autonomy.